Does lead userness foster idea implementation and diffusion? A study of internal shopfloor users - Schweisfurth, Tim G.; Dharmawan, Magha P. (Research Policy, 2019)
While the relevance of lead users has been well established for the early phases of the innovation process, such as ideation and creativity, the relationship between lead userness and implementation and diffusion has not been investigated. This is surprising, as the conjecture that lead user ideas are more likely to be implemented and diffused than non-lead user ideas is a key tenet of lead user research. To test this conjecture we draw on a sample of 87 internal process users in a large electronics firm who submitted ideas to an idea management system. 452 ideas were suggested, of which 148 were implemented and 33 further diffused on the shopfloor. We find that higher lead userness is positively and significantly associated with the likelihood of suggested ideas being implemented and diffused. This effect is substantial: Ideas coming from lead users were more than two times more likely to be implemented and more than three times more likely to be diffused than ideas coming from non-lead users. We conclude that lead user ideas are more likely than non-lead user ideas to be implemented and diffused throughout a social system, which arguably constitutes the ultimate success of any idea. Our research contributes to research on (internal) lead users, idea management systems, and idea implementation and diffusion.